2021
DOI: 10.1038/s41438-021-00549-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing reveals rare off-target mutations in CRISPR/Cas9-edited grapevine

Abstract: The CRISPR (clustered regularly interspaced short palindromic repeats)-associated protein 9 (Cas9) system is a powerful tool for targeted genome editing, with applications that include plant biotechnology and functional genomics research. However, the specificity of Cas9 targeting is poorly investigated in many plant species, including fruit trees. To assess the off-target mutation rate in grapevine (Vitis vinifera), we performed whole-genome sequencing (WGS) of seven Cas9-edited grapevine plants in which one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 51 publications
(90 reference statements)
3
18
0
Order By: Relevance
“…The VqWRKY31 cDNA was cloned by PCR using the primers 2300flg -WRKY31 (forward) and 2300flg -WRKY31 (reverse) ( Supplementary Table S1 ) and then inserted into the pCambia2300 vector downstream of the CaMV35S promoter to generate CaMV35S- VqWRKY31 -3 × Flag. A. tumefaciens GV3101 harboring 35S- VqWRKY31 -3 × Flag was used for the stable transformation of grapevine via previously described methods [ 31 ]. Young vegetative shoots from transgenic plants were transferred to agar-solidified MS medium every 2 months for rapid propagation.…”
Section: Methodsmentioning
confidence: 99%
“…The VqWRKY31 cDNA was cloned by PCR using the primers 2300flg -WRKY31 (forward) and 2300flg -WRKY31 (reverse) ( Supplementary Table S1 ) and then inserted into the pCambia2300 vector downstream of the CaMV35S promoter to generate CaMV35S- VqWRKY31 -3 × Flag. A. tumefaciens GV3101 harboring 35S- VqWRKY31 -3 × Flag was used for the stable transformation of grapevine via previously described methods [ 31 ]. Young vegetative shoots from transgenic plants were transferred to agar-solidified MS medium every 2 months for rapid propagation.…”
Section: Methodsmentioning
confidence: 99%
“…Potentially deleterious off-target activity can occur in regions of the genome that share sequence identity with the target site such as duplicated/repeated sequences [107]. Off-target effects are often undesirable and have been observed in rice (Oryza sativa) [108], grapevine (Vitis vinifera) [109], and cotton (Gossypium) [110]. Avoiding off-target effects requires detailed genomic information for the individual being modified [107].…”
Section: Off-targets Effects In Multiplexed Editingmentioning
confidence: 99%
“…Recent reports in animal models using long-read sequencing demonstrated that unexpected on-target damage of CRISPR was far more serious and widespread than anticipated [217,218] and revealed unforeseen CRISPR-Cas9 off-target activity [219,220]. Recently, high-throughput whole-genome resequencing has been used to evaluate off-target edits and untargeted mutations in Arabidopsis [221], rice [222,223], tomato [224], cotton [225], and grapevine [226], confirming that the off-target CRISPR-Cas9-induced mutations are rare in plants and smaller in magnitude than the variation that is generated by conventional tissue culturing or mutation breeding [227]. However, one possible limitation of the whole-genome resequencing approach for screening a large number of potential off-target sites is that it requires a reference genome.…”
Section: Future Challenges and Concluding Remarksmentioning
confidence: 99%